Population genomic evidence for adaptive differentiation in Baltic Sea three-spined sticklebacks - Guo, Baocheng; DeFaveri, Jacquelin; Sotelo, Graciela; Nair, Abhilash; Merilä, Juha (BMC biology, 2015)
The degree of genetic differentiation among populations experiencing high levels of gene flow is expected to be low for neutral genomic sites, but substantial divergence can occur in sites subject to directional selection. Studies of highly mobile marine fish populations provide an opportunity to investigate this kind of heterogeneous genomic differentiation, but most studies to this effect have focused on a relatively low number of genetic markers and/or few populations. Hence, the patterns and extent of genomic divergence in high-gene flow marine fish populations remain poorly understood. We here investigated genome-wide patterns of genetic variability and differentiation in 10 marine populations of three-spined stickleback (Gasterosteus aculeatus) distributed across a steep salinity and temperature gradient in the Baltic Sea, by utilizing > 30,000 single nucleotide polymorphisms obtained with a pooled RAD-seq approach. We found that genetic diversity and differentiation varied widely across the genome, and identified numerous fairly narrow genomic regions exhibiting signatures of both divergent and balancing selection. Evidence was uncovered for substantial genetic differentiation associated with both salinity and temperature gradients, and many candidate genes associated with local adaptation in the Baltic Sea were identified. The patterns of genetic diversity and differentiation, as well as candidate genes associated with adaptation in Baltic Sea sticklebacks were similar to those observed in earlier comparisons between marine and freshwater populations, suggesting that similar processes may be driving adaptation to brackish and freshwater environments. Taken together, our results provide strong evidence for heterogenic genomic divergence driven by local adaptation in the face of gene flow along an environmental gradient in the post-glacially formed Baltic Sea.